Does the Sharing Economy do any Good? - Dillahunt, Tawanna R.; Terveen, Loren; Lampinen, Airi; Kendrick, Cory; O'Neill, Jacki (ACM - Association for Computing Machinery, 2016)
Despite the benefits offered by sharing economy, researchers have identified several challenges preventing disadvantaged groups (e.g. low socioeconomic status, un(der)employed and/or users from emerging regions) from receiving the same level of benefits as those from advantaged populations. This panel brings researchers from the sharing economy and mobile crowdsourcing space whose research has identified unique challenges for underserved populations. We consider the opportunities offered by these platforms to disadvantaged communities and examine to what extent these platforms instead may recreate disadvantage, as well as the workarounds communities employ to make these platforms work for them. We examine the opportunities for the CSCW community to address these challenges going forward.